Carbon and sulfur isotopic compositions of basal Datangpo Formation, northeastern Guizhou, South China： Implications for depositional environment - Chen, Xi; Li, Da; Ling, Hong-Fei; Jiang, Shao-Yong (Progress in natural science, 2008)
Isotopic compositions of Mn-carbonate and organic carbon from the same individual samples and sulfur isotopic compositions of pyrites in the basal Datangpo Formation were analyzed. Highly 34S-enriched pyrites （834Spyrite =31.7-59.4‰） were precipitated in rel- atively occlusive pore water under anoxic condition in sediments, which is consistent with the observation of large and scattered pyrite framboids. The sulfidic deep ocean was not ＂oxidized＂ in the early Datangpo interglacial interval, thus the level of seawater sulfate remained low and marine δ34Ssulphate remained high. Low δ13Ccar （average -7.4‰） and abnormal relationship between δ13Ccar and fractionation （ΔCar-ors） imply that the negative δ13CCar excursion may have resulted from oxidation of part of a large organic carbon reservoir. High Δcar-org （average 25.1‰） implicates high CO2 level in the atmosphere. Small standard deviation （1.0‰） of δ13CCar values indicates the Mn-carbonate was precipitated near the water-sediment interface under dysoxic conditions rather than in occlusive pore water in sediments.